Aerodynamic Characteristic Analysis of V-22 Tilt-Rotor Aircraft in Hover. Issue 1 (1st June 2022) - Xu, Peimin; Yang, Yueyue; Zhou, Jie; Zhou, Guiyu
Abstract: Tilt-rotor aircraft combines the vertical take-off and landing function of helicopters with the high-speed cruise function of fixed-wing aircraft, which has given rise to extensive attention in the aviation field, but the complex aerodynamic characteristics of the rotor flow field and the interference of rotor/fuselage have always been tough problems. In recent years, the continuous development of high-performance computer and the combination of high-precision CFD method and dynamic overset grid technology, make it possible to perform fine numerical simulation of tilt-rotor aircraft's flow field. In this paper, the low-dissipation fifth-order Roe-WENO scheme and overset grid method are used to solve the unsteady N-S equation, and the hovering state of tilt-rotor aircraft is numerically simulated. The result shows: under the interference of ground effect and fountain effect, the lift coefficient of blade when the azimuth angle is 180° to 360° is obviously smaller than that when the azimuth angle is 0° to 180°. The vortex structure of the hovering flow field of V-22 tilt-rotor aircraft is mainly composed of the fountain effect recirculation zone, the tip vortex wake and the root vortex wake. The tip vortex wake develops downwards, shrinks inward and approaches the fuselage. After the root wake falls off, it converges and fuses on the surface of nacelles. The root vortex wake is strong and moves towards the front of the fuselage and the plane of symmetry.